Is Growth an Information Technology Story in Europe Too? - Francesco Daveri (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
While the return to growth in the US is largely credited to the rapid spreading of information technology, a key policy concern everywhere, and notably in Europe, is whether and when the US economic boom will extend abroad, and what role new technologies are about to play. In this paper, I collect and supplement data on the extent and the contribution to growth of new economy activities in Europe, and in a sample of OECD countries at large, in the 1990s. Available evidence indicates that capital accumulation in information technologies did make a contribution to growth in the EU too, though not equally everywhere. The contribution of new technologies was substantial in the UK and the Netherlands, and rapidly increasing over time in Finland, Ireland and Denmark. These were also the fast EU growing countries in the 1990s. New technologies contributed less in France, Germany, Belgium and Sweden, and marginally in Italy and Spain. Most of these countries were also slow growers. I conclude that the growth gaps between the EU and the US, as well as within the EU, can (also) be associated to the diverse pace of adoption of new technologies across countries.
Keywords: 330